Research on Dynamic Characteristics of Robot Joint System Under Impact Load - Shuai Mo; Xu Li; Zhenning Yang; Changpeng Zhou; Guojian Cen; Yunsheng Huang (Jixie chuandong)
In order to study the electromechanical coupling mechanism of the micro-robot joints in the unsteady working state and considering the time-varying stiffness and error of gear meshing， a lumped parameter method is adopted to establish an electromechanical coupling model of the motor-driven two-stage series planetary gear transmission system. The influence of the natural frequency， and quality parameters of the system on the natural frequency of the system and the distribution law of modal energy is calculated and the torsional vibration characteristics of the gear system under impact load are analyzed. The research results show that as the quality of parts increases， the natural frequency of the system shows a downward trend. The modal energy of the system is mainly manifested as low-order torsional vibration strain energy and high-order kinetic energy. During the impact process， the system behaves as a vibration mode dominated by a first-order natural frequency and a one-time meshing frequency.